‘One Health’ Approach to Infectious Diseases and Prevention of Antimicrobial Resistance: A Review - Nurunnabi, Abu Sadat Mohammad; Mozaffor, Miliva; Sweety, Afroza Akbar; Kabir, Md Rashedul; Sharmin, Saida; Kabir, Nahid (Bangladesh Journal of Medical Microbiology, 2023)
This review paper aims to provide an understanding on current concepts of ‘One Health’ approach in the field of public health with a special focus on infectious diseases and prevention of antimicrobial resistance. 'One Health' is an approach to designing and implementing programmes, policies, legislation, and research in which multiple sectors communicate and work together to achieve better public health outcomes. The scope of ‘One Health’ includes zoonotic diseases, antimicrobial resistance, food safety and security, vector-borne diseases that come from insect bites or animals, environmental contamination, and other health threats shared by people, animals, and the environment. The World Health Organization (WHO) is working closely with the Food and Agriculture Organization of the United Nations (FAO) and the World Organization for Animal Health (OIE) to promote multi-sectoral responses to food safety hazards, risks from zoonoses, and other public health threats at the human-animal-ecosystem interface and provide guidance on how to reduce those risks for a better living in our planet Earth. Our medical education curriculum should also offer a first exposure to both the concepts of ‘One Health’ and the collaborative processes required to manage issues associated with human, animal, and environmental health. Bangladesh Journal of Medical Microbiology, January 2022;16(1):25-30